2021
DOI: 10.1002/hep.31601
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Perioperative Serotonin Reuptake Inhibitor Treatment During Hepatic Surgery

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Increasing evidence suggests that platelets are important mediators in HCC carcinogenesis [ 26 , 29 , 30 , 31 ]. In fact, inhibition of platelet function has been correlated with reduced risks of HCC in both animal models [ 32 ] and patients with cirrhosis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that platelets are important mediators in HCC carcinogenesis [ 26 , 29 , 30 , 31 ]. In fact, inhibition of platelet function has been correlated with reduced risks of HCC in both animal models [ 32 ] and patients with cirrhosis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mawardi et al found that SNRI use independently increases risk of gastrointestinal bleeding in LVAD patients [65]. Recent research also suggests that SSRIs/SNRIs may be associated with poor postoperative outcomes following hepatic resection, and should be held in the perioperative period [66].…”
Section: Intraoperative Considerationsmentioning
confidence: 98%
“…Platelet-derived 5-HT is an important mediator of liver regeneration, most likely through production of growth factors at the site of injury ( 160 , 161 ). Recently a multi-center trial has demonstrated that perioperative use of selective serotonin reuptake inhibitors and serotonin noradrenaline reuptake inhibitors is associated with adverse outcomes after hepatic resection further supporting a role for 5-HT ( 162 ).…”
Section: The Role Of Platelets In Resolution Of Inflammationmentioning
confidence: 99%